2008
DOI: 10.1371/journal.pone.0001789
|View full text |Cite
|
Sign up to set email alerts
|

Cardiomyocyte Formation by Skeletal Muscle-Derived Multi-Myogenic Stem Cells after Transplantation into Infarcted Myocardium

Abstract: BackgroundCellular cardiomyoplasty for myocardial infarction has been developed using various cell types. However, complete differentiation and/or trans-differentiation into cardiomyocytes have never occurred in these transplant studies, whereas functional contributions were reported.Methods and ResultsSkeletal muscle interstitium-derived CD34+/CD45− (Sk-34) cells were purified from green fluorescent protein transgenic mice by flowcytometory. Cardiac differentiation of Sk-34 cells was examined by in vitro clon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 34 publications
5
48
0
Order By: Relevance
“…Previous studies have shown that stem cells isolated from skeletal muscle specimens have the ability to differentiate into CMs; 8,14,[16][17][18][19] however, the efficiency of CM differentiation remains unclear and with limited functional characterization. In the current study we found that (1) low-serum growth medium-treated rat MDSCs expressed cardiacspecific genes similar to native adult myocardium, consistent with the findings of others in both human and mouse skeletal muscle-derived cells, and (2) the combination of MDSC-aggregate formation and 3DGB culture significantly increased cardiac-specific protein expression, spontaneous beating cell activity, and contractile properties.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that stem cells isolated from skeletal muscle specimens have the ability to differentiate into CMs; 8,14,[16][17][18][19] however, the efficiency of CM differentiation remains unclear and with limited functional characterization. In the current study we found that (1) low-serum growth medium-treated rat MDSCs expressed cardiacspecific genes similar to native adult myocardium, consistent with the findings of others in both human and mouse skeletal muscle-derived cells, and (2) the combination of MDSC-aggregate formation and 3DGB culture significantly increased cardiac-specific protein expression, spontaneous beating cell activity, and contractile properties.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, a skeletal muscle precursor population was isolated via FACS sorting CD45 Ϫ , Sca1, Mac1, CXCR4 ϩ , and ␤1 integrin ϩ subpopulations of satellite cells (Cerletti et al, 2008), and a myogenic endothelial cell population in skeletal muscle was initially reported based on CD34 ϩ and CD45 Ϫ expression, which was shown to improve cardiac function after myocardial infarction (Tamaki et al, 2002(Tamaki et al, , 2008a. Tamaki et al (2007Tamaki et al ( , 2008b have also clonally isolated so-called skeletal double-negative cells (Sk-DN), which are CD34 Ϫ /CD45 Ϫ , and have demonstrated their multipotency in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, skeletal myoblast engraftment may be combined with bone marrow stem cell transplantation for mutual beneficial effect of the two cell types (71). Studies are already underway to subfractionate and purify more primitive populations from the two cell types and showing multilineage differentiation potential, including cardiac lineage (114).…”
Section: Adult Stem Cells In Cardiovascular Therapymentioning
confidence: 99%